ESSENCE AND PRINCIPLES OF RISK MANAGEMENT CONCEPT - Lahunova I.A.; Leonova O.O. (Pressing Problems of Public Administration, 2018)
The paper considers the essence and principles of risk management, the concepts that allow, due to adequate arrangement of a management process, achieving  nancial stability, high competitiveness, effective impact on risks which promotes a successful functioning of an organization and its stable income. Risk management is connected with both negative and favorable consequences. The essence of risk management lies in identifying potential deviations from planned results and in control of these deviations with the aim of providing prospects, reducing losses and a better substantiation of decisions made. To manage risks means to outline the prospects and  nd opportunities for improvement of activities, and also to avoid or reduce the probability of unfavorable course of events.